Androgenic Modulation of the Chloride Transporter NKCC1 Contributes to Age-dependent Isoflurane Neurotoxicity in Male Rats. (October 2020) - Chinn, Gregory A.; Sasaki Russell, Jennifer M.; Yabut, Nicole A.; Maharjan, Deenu; Sall, Jeffrey W.
Abstract : Background: Cognitive deficits after perinatal anesthetic exposure are well established outcomes in animal models. This vulnerability is sex-dependent and associated with expression levels of the chloride transporters NKCC1 and KCC2. The hypothesis was that androgen signaling, NKCC1 function, and the age of isoflurane exposure are critical for the manifestation of anesthetic neurotoxicity in male rats. Methods: Flutamide, an androgen receptor antagonist, was administered to male rats on postnatal days 2, 4, and 6 before 6 h of isoflurane on postnatal day 7 (ntotal = 26). Spatial and recognition memory were subsequently tested in adulthood. NKCC1 and KCC2 protein levels were measured from cortical lysates by Western blot on postnatal day 7 (ntotal = 20). Bumetanide, an NKCC1 antagonist, was injected immediately before isoflurane exposure (postnatal day 7) to study the effect of NKCC1 inhibition (ntotal = 48). To determine whether male rats remain vulnerable to anesthetic neurotoxicity as juveniles, postnatal day 14 animals were exposed to isoflurane and assessed as adults (ntotal = 30). Results: Flutamide-treated male rats exposed to isoflurane successfully navigated the spatial (Barnes maze probe trial F[1, 151] = 78; P < 0.001; mean goal exploration ± SD, 6.4 ± 3.9 s) and recognition memory tasks (mean discrimination index ± SD, 0.09 ± 0.14; P = 0.003), unlike isoflurane-exposed controls. Flutamide changed expression patterns of NKCC1 (mean density ± SD: control, 1.49 ± 0.69; flutamide, 0.47 ± 0.11; P < 0.001) and KCC2 (median density [25th percentile, 75th percentile]: control, 0.23 [0.13, 0.49]; flutamide, 1.47 [1.18, 1.62]; P < 0.001). Inhibiting NKCC1 with bumetanide was protective for spatial memory (probe trial F[1, 162] = 6.6; P = 0.011; mean goal time, 4.6 [7.4] s). Delaying isoflurane exposure until postnatal day 14 in males preserved spatial memory (probe trial F[1, 140] = 28; P < 0.001; mean goal time, 6.1 [7.0] s). Conclusions: Vulnerability to isoflurane neurotoxicity is abolished by blocking the androgen receptor, disrupting the function of NKCC1, or delaying the time of exposure to at least 2 weeks of age in male rats. These results support a dynamic role for androgens and chloride transporter proteins in perinatal anesthetic neurotoxicity. Abstract : Blockade of androgen receptors in 7-day-old male rats protects against isoflurane anesthesia-induced behavioral deficits. Androgen receptor blockade results in a premature transition in the developmental expression profiles of chloride transporters NKCC1 and KCC2. These observations suggest that regulation of specific chloride transporters, determining functional modalities of γ-aminobutyric acid–mediated neurotransmission, by androgens is a critical component for developmental anesthetic neurotoxicity.Supplemental Digital Content is available in the text.